Strategi Segmentasi, Penargetan, dan Posisi (STP) Starbucks: Mempertahankan Kepemimpinan di Industri Kopi Global di Tengah Tantangan dan Peluang - Fitroh, Ike Silvia; Shodiq, Ahmad Fajar; Rahayu, Yayuk Sri (Maliki Interdisciplinary Journal, 2025)
This research explores the segmentation, targeting, and positioning (STP) strategies employed by Starbucks to sustain its position as a leader in the global coffee industry. Through the STP approach, Starbucks effectively identifies strategic market segments, employs robust targeting methods, and establishes a strong brand position by delivering premium products, unique customer experiences, and a commitment to sustainability. The study also addresses the challenges and opportunities Starbucks faces, including fierce competition and evolving consumer preferences for healthier and plant-based products. Recommendations emphasize enhancing product innovation, bolstering digital marketing strategies, and maintaining a strong focus on sustainability to preserve competitive advantage.